HUBUNGAN ANTARA KADERISASI DAN IDEOLOGI DALAM PARTAI POLITIK: STUDI KASUS AKTIVITAS INTERNAL PDIP - Arfan Fadhillah Danuwidjaja; Firman Manan (Epistemik Press, 2023)
Caderization and ideology are important aspects of a political party, especially in the activities of a political party. Ideology primarily plays an important role as the philosophical foundation of a political party. Regeneration can then be seen as fulfilling this goal in the philosophical context of political parties. The relationship between cadre formation and the ideology of a political party then becomes important to explore how the two concepts rub against one another. This article was specifically created with the aim of exploring how ideology influences the regeneration activities of a party, and whether regeneration activities are carried out with the philosophical principles that exist in the ideology of political parties. This is specifically done using qualitative research methods based on data and information directly obtained from case studies of the internal activities of the Indonesian Democratic Party of Struggle. Overall, the results of the research in this article found that the relationship between cadre formation and ideology in political parties is practically centered on efforts to generate good public perceptions of political parties and the ideology espoused by these parties.